Reading people [compact disc, unabridged] : how seeing the world through the lens of personality changes everything - Bogel, Anne, 1978- (christianaudio, 2017)
Anne Bogel shares specific, practical real-life applications across all facets of life, including love and marriage, productivity, parenting, the workplace, and spiritual life. In her friendly, relatable style, Bogel shares engaging personal stories that show firsthand how understanding personality can revolutionize the way people live, love, work, and pray.